2019
DOI: 10.1002/jez.2254
|View full text |Cite
|
Sign up to set email alerts
|

DnaJ chaperones contribute to canalization

Abstract: Canalization, an intrinsic robustness of development to external (environmental) or internal (genetic) perturbations, was first proposed over half a century ago. However, whether the robustness to environmental stress (environmental canalization [EC]) and to genetic variation (genetic canalization) are underpinned by the same molecular basis remains elusive. The recent discovery of the involvement of two endoplasmic reticulum (ER)‐associated DnaJ genes in developmental buffering, orthologues of which are conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Supporting this, the 15 MDBGs include genes involved in the cell cycle (KY.Chr2.1529, Leucine aminopeptidase 3 (LAP3)), translation, stress response (KY.Chr2.2295, catalase), degradation in homeostasis (KY.Chr6.691, glycosylated lysosomal membrane protein (GLMP)), innate immunity (KY.Chr14.407; interferon regulatory factor 2 (IRF2)) and metabolism (Chr2.1046; galactocerebrosidase; KY.Chr9.550, speedy protein; Chr7.688, serine protease 27 (PRSS27)), while we did not find any transcription factors that are involved in development (Additional file 2: Table S4). We note that one of the other MDBGs, DnaJC10, was previously shown to be involved in canalization [6,7].…”
Section: Identification Of Maternal Developmental Buffering Genes (Md...mentioning
confidence: 72%
See 1 more Smart Citation
“…Supporting this, the 15 MDBGs include genes involved in the cell cycle (KY.Chr2.1529, Leucine aminopeptidase 3 (LAP3)), translation, stress response (KY.Chr2.2295, catalase), degradation in homeostasis (KY.Chr6.691, glycosylated lysosomal membrane protein (GLMP)), innate immunity (KY.Chr14.407; interferon regulatory factor 2 (IRF2)) and metabolism (Chr2.1046; galactocerebrosidase; KY.Chr9.550, speedy protein; Chr7.688, serine protease 27 (PRSS27)), while we did not find any transcription factors that are involved in development (Additional file 2: Table S4). We note that one of the other MDBGs, DnaJC10, was previously shown to be involved in canalization [6,7].…”
Section: Identification Of Maternal Developmental Buffering Genes (Md...mentioning
confidence: 72%
“…The idea of environmental canalization has been a matter of debate over the past half a century. In addition to chaperone proteins [2][3][4][5][6][7], various other molecules and potential mechanisms have been identified as relevant to environmental canalization (see reviews, [8][9][10]). Other studies suggested that canalization is a property of gene networks [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a C. elegans study showed that seven of eight endoplasmic reticulum associated DNAJ genes are involved in trait canalization. [ 20 ] It is important to note that an independent allele at the same locus ( ghost‐2 ), as well as two CRISPR/CAS9‐generated mutations had leaf variegation but did not exhibit the unstable variegation phenotype. ghost‐2 produced uniformly large plants and the CRISPR/CAS9 mutants did not survive beyond the first true leaf stage.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp-90-mediated buffering of protein folding has been thought to influence the variable expressivity of human disease 56 . In the seam, RNAi knockdown of hsp-90 or DnaJ chaperones leads to increased variability in SCN 10 , 57 . Differences in heat shock protein expression have also been shown to affect the incomplete penetrance of mutations 23 , 58 .…”
Section: Discussionmentioning
confidence: 99%